2015
DOI: 10.1080/11250003.2015.1091897
|View full text |Cite
|
Sign up to set email alerts
|

The influence of environmental variables on soil mite communities (Acari: Mesostigmata) from overgrazed grassland ecosystems – Romania

Abstract: In 2013-2014, the soil mite communities from six overgrazed grassland ecosystems located in the Trascău Mountains, Romania, were investigated. Forty-six species were identified, with 645 individuals. Some abiotic factors from soil were measured (soil temperature -T, soil water content -H, soil acidity -pH, carbon content -C, total nitrogen -Nt, and C/Nt ratio). Significant statistical differences were obtained between environmental factors. Using a canonical correspondence analysis of mite species abundance, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…Low importance of other parameters, especially light availability, which is claimed to drive soil temperature (by canopy transmittance; von Arx et al 2012 ), was unexpected. The studies of Manu et al ( 2016 ) indicated that temperature was a significant factor for some Mesostigmata such as Protogamasellus pygmaeus or Trachytes irenae . This could indicate that the major factor that influenced species richness near the Czerwona Woda River was soil organic layer depth, which is connected with soil pH and primarily to the tree species.…”
Section: Discussionmentioning
confidence: 99%
“…Low importance of other parameters, especially light availability, which is claimed to drive soil temperature (by canopy transmittance; von Arx et al 2012 ), was unexpected. The studies of Manu et al ( 2016 ) indicated that temperature was a significant factor for some Mesostigmata such as Protogamasellus pygmaeus or Trachytes irenae . This could indicate that the major factor that influenced species richness near the Czerwona Woda River was soil organic layer depth, which is connected with soil pH and primarily to the tree species.…”
Section: Discussionmentioning
confidence: 99%
“…Mountain grasslands of Romania are critical from ecological and pastoral points of view. They are defined by valuable species of plants and animals that often have ecological plasticity [ 10 , 11 , 12 , 13 , 14 , 15 ]. These ecosystems are exposed to degradation processes through overgrazing, leading to changes in floristic composition, being dominated by Nardus stricta , a useless species for livestock, such as cows.…”
Section: Introductionmentioning
confidence: 99%
“…Research studies from all over the world revealed that the Mesostigmata communities correlated with environmental variables could constitute a very useful biological tool to characterized the ecological quality of terrestrial ecosystems and the quality of soils 9,10,18,21,[25][26][27][29][30][31]33 . In the case of urban green areas from Bucharest, under different management scenarios, their ecological characterization was made taking into account the variation of the environmental parameters, in correlation with spatial dynamics of the communities' parameters of Mesostigmata fauna (species diversity and numerical abundance).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, they are the main regulator of the other soil invertebrate populations 11 , 24 , 25 . Most species prefer habitats rich in organic matter, with high soil moisture, medium soil temperature and a low pH 26 28 . Because of these ecological requirements and their marked sensitivity to environmental/anthropogenic disturbance, soil mites are often used as soil bioindicators 15 , 29 33 .…”
Section: Introductionmentioning
confidence: 99%